Analysis of Networking Tools Using Cisco Packet Tracer (CPT) - Thoyyibah. T; Hidayat, Asep Ridwan; Hanggara, Imam Satria; Sudarsono, Rizki Satriawan (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2024)
This study aims to evaluate the performance and effectiveness of network devices using Cisco Packet Tracer (CPT) as a simulation tool. CPT is a widely utilized network simulation software, commonly employed for designing and testing network configurations prior to real-world implementation. This research investigates various network topologies to assess the performance of devices such as routers, switches, and end devices. The research methodology encompasses the design of network scenarios, device configuration, and testing of various network protocols. The analysis reveals that CPT is capable of accurately replicating most functions and behaviors of network devices, providing a clear depiction of network performance under different conditions. The findings suggest that CPT serves as an effective and efficient tool for both educational purposes and network planning, despite certain limitations in features and realism when compared to actual hardware. This study is expected to offer valuable insights for professionals and academics in understanding and optimizing network design before deployment in real-world environments.